Comparison of setups for measuring the viscosity of coal ash slags for entrained-flow gasification. (1st January 2022) - Laabs, Marcel; Schwitalla, Daniel Harry; Ge, Zefeng; Kong, Lingxue; Bai, Jin; Guhl, Stefan; Meyer, Bernd
Highlights: The different viscosity measurement routines are compared for uniformed test routines. Study of property changes due to slag viscosity measurement employing AFT, XRF, XRD, SEM-EDX. Shear-induced crystallization demonstrated for coal ash slag. Abstract: A coal ash and a process slag from an entrained-flow gasifier were analyzed by two institutes in their respective workflow to compare viscosity measurement techniques under reducing conditions. Several analyses were carried out to characterize the samples, including X-ray fluorescence (XRF), X-ray diffraction (XRD) and scanning electron microscopy with an energy-dispersive X-ray detector (SEM-EDX). The results are compared to the phases predicted based on thermochemical calculations. A coal slag (S1) was analyzed as exhibiting Newtonian behavior by one institute, while it showed shear-thickening behavior at another institute due to crystallization. This was confirmed by XRD and SEM-EDX. In contrast to previous studies, the sample in this work was still glassy at a low shear rate. The phase compositions of the crystallized slags were in good agreement with thermochemical predictions. The process slag (S2) sample showed shear-thinning behavior but was of very high viscosity, meaning that the measurement was restricted by instrumental limitations. The chemical compositions of the slags obtained after viscosity measurements indicated contamination with crucible material (Mo) for S1, while the composition of S2 was the same before and after viscosity measurements. The overall relative difference in the measurements considering both measurement routines and both samples was ±22%.